Preliminary revision of the Physical Education Grit Scale in Chinese athletes - Zhang, Renfang; Gao, Shenmao; Dou, Guangbo (Frontiers in Psychology, 2023)
Objective: The work aimed to revise the Physical Education Grit Scale (PE-Grit) applicable to Chinese athletes. Methods: Five hundred and thirty-eight professional athletes from Chinese Sports Colleges and provincial sports teams were selected by cluster random sampling. Then, PE-Grit was analyzed for project analysis, exploratory factor analysis, confirmatory factor analysis, criterion-related validity analysis, and reliability analysis. Results: Independent sample t-test and item-total correlation analysis of the questions showed that 16 items of the scale had good discrimination. The confirmatory factor analysis model showed that: Firstly, the factor structure consisted of 2 subscales and 4 dimensions (χ2/df=1.827; CFI= 0.961; TLI=0.953; IFI=0.961; RMSEA=0.051). Moreover, Cronbach's coefficient α of the total scale and the 4 dimensions were between 0.751 and 0.865. A significant positive correlation existed between PE-Grit, and self-control, which showed good criterion-related validity. Conclusion: Revised PE-Grit can measure Chinese athletes' physical education grit for its good reliability and validity.